A política nacional de educação inclusiva: um estudo de escolas da rede municipal de Gurinhém/PB - Almeida, Welita Gomes de (2010)
This work approaches the National Politic of Inclusion Education published in 2008 for the Ministry of the Education and Secretariat of Special Education MEC/SEESP. Our objective is analyze the speeches of the teachers about the National Politic of Inclusion Education and the development in regular schools in Gurinhém, Paraiba, being taken as base the following aspects: accessibility, curriculum, specialized attendance and formation of teachers. The option was based in theorycal- methodological in approach pos structural as the conception of identity and difference. The basis of research are inclusion, identity, difference, curriculum, politic and some ways of inclusion: Hall (2006), Tomaz Tadeu (2008), Skliar (2003), Costa (2002), Corazza (2002), Pereira (2006, 2009), Dorziat (2006, 2009), Santos (2008), Carvalho (2004), Laplane (2004), Silva (2001), Ferreira (2004), and others. This study if it characterizes of the methodological point of view in a research of qualitative character, which used survey and revision of literature and research of field. The field of the research was composed for two schools of the municipal net of Gurinhém, Paraíba, and the instrument used for collection of data was to the interview half-structuralized applied individually for a sample of seven teachers of regular school. We opt to the analysis of the speech while methodology of treatment and analysis of data, on the basis of the social theory of the speech of Fairclough (2008), that it analyzes the speech in a three-dimensional picture, as text, practical social practical discursive and. Our considerations in this study is an appear about the official speech of politic because Inclusion Education is grow in Brazil and the legislation are better, the purpose is education for ale, include the deficient‟s but the teachers said that the reality in the schools is different, the ideas are different, the proposal of inclusion.